2018
DOI: 10.1016/j.jbusres.2017.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Art, science and organisational interactions: Exploring the value of artist residencies on campus

Abstract: This case study examines how an artist residency at an aquaculture institute within a university creates value on campus and beyond. We find that the residency, initially regarded as 'risk-taking' by both artist and institute, created unexpected opportunities stemming from the synergies between art and science. We find that 'new ways of seeing' aquaculture science resulted in the creation of aesthetic, emotional, environmental, educational and social values embracing the intrinsic, instrumental, and institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…For example, the predecessor of Songshan cultural and innovative park is Songshan Tobacco Factory. These cultural and innovative industrial parks have achieved innovative progress in the field of cultural and innovative industries by using their own historical background and characteristics and combining traditional process concepts [ 15 ]. Zhang and Wang believe that it is necessary to combine innovative ideas and experiential design, that is, what the audience needs is not only the beauty of the product itself but also the emotional design concept, so as to enhance the interaction between the product and the user, so as to meet the psychological satisfaction of the user [ 16 ].…”
Section: Related Workmentioning
confidence: 99%
“…For example, the predecessor of Songshan cultural and innovative park is Songshan Tobacco Factory. These cultural and innovative industrial parks have achieved innovative progress in the field of cultural and innovative industries by using their own historical background and characteristics and combining traditional process concepts [ 15 ]. Zhang and Wang believe that it is necessary to combine innovative ideas and experiential design, that is, what the audience needs is not only the beauty of the product itself but also the emotional design concept, so as to enhance the interaction between the product and the user, so as to meet the psychological satisfaction of the user [ 16 ].…”
Section: Related Workmentioning
confidence: 99%
“…In terms of broader support, the institution we investigated also offers funded artist residencies held at other art venues in the UK and overseas. However, it is also possible for artists elsewhere to hold residencies in universities and industrial settings where unexpected opportunities are created and developed through new ways of seeing at individual and organisational levels (Lee, Fillis and Lehman, 2018). These residences can be viewed as a critical lens on the organisation and its practices, where the artist helps create a positive change (Antal, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…They reviewed commonly used instruments such as College and University Classroom Environment Inventory, the Work Environment Inventory, the Team Climate Inventory and the Situational Outlook Questionnaire while Ceylan et al (2008) suggested the photographic technique as their method. Besides, various studies have been conducted on individuals used in institutions with artistic or administrative backgrounds to determine individuals' need for creativity or to provide a model or method for the relationship between the parameters affecting creativity (De Paoli et al, 2017;García-García et al, 2019;Lee et al, 2018;Lee, 2016). These surveys are conducted with a questionnaire or face-to-face or telephone interview to investigate creativity.…”
Section: Methodsmentioning
confidence: 99%
“…The model in Figure 1 shows the role of the physical work environment as an independent variable in the creative process and the creative product. In fact, artist residencies, if planned thoughtfully, have the potential to create an innovative and creative culture (Lee et al, 2018).…”
Section: F 3913/14mentioning
confidence: 99%